1994
DOI: 10.1007/bf00128603
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase production by carbon and nitrogen sources fed-batch culture of Arthromyces ramosus

Abstract: Carbon and nitrogen sources were investigated for improving peroxidase production by Arthromyces ramosus, a hyperproducer of peroxidase. Glucose as carbon source and a mixture of yeast extract and polypeptone at the ratio of 3 to 5 as nitrogen source in a production medium were shown to give the highest peroxidase activity. During the culture amino acids such as alanine, arginine, methionine, leucine, tyrosine and tryptophan were depleted. Therefore, glucose supplemented nitrogen source fed-batch culture was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Most white rot fungi, including Phanerochaete chrysosporium, start lignin degradation when nitrogen, carbon, or sulfur becomes limiting (12). Peroxidase production from Arthromyces ramosus is greatest when glucose and yeast extract or polypeptone are added at a ratio of 3:5 (41). The production of manganese peroxidase by the white rot fungus Lentinus edodes is suppressed by a high nitrogen concentration in the medium, whereas under these conditions laccase production reached its maximum level (3).…”
Section: Discussionmentioning
confidence: 99%
“…Most white rot fungi, including Phanerochaete chrysosporium, start lignin degradation when nitrogen, carbon, or sulfur becomes limiting (12). Peroxidase production from Arthromyces ramosus is greatest when glucose and yeast extract or polypeptone are added at a ratio of 3:5 (41). The production of manganese peroxidase by the white rot fungus Lentinus edodes is suppressed by a high nitrogen concentration in the medium, whereas under these conditions laccase production reached its maximum level (3).…”
Section: Discussionmentioning
confidence: 99%
“…Nidadavolu et al, (2010) were found that the best extraction ratio for peroxidase from discarded mushroom beds was 1:1 and 1:2. While (Tsujimura et al, 1994), shown the best ratio was 1:5 for peroxidase extraction from Arthromyces ramosus.s…”
Section: The Optimum Ratio Of Peroxidase Extractionmentioning
confidence: 96%
“…Nidadavolu et al, (2010) 23 were found that the best extraction ratio for peroxidase purified from discarded mushroom beds was 1:1 and 1:2. While Tsujimura et al,(1994) 24 extracted peroxidase from Arthromycesramosus with 1:5 ratio.…”
Section: The Optimum Ratio Of Peroxidase Extractionmentioning
confidence: 99%